Delinquent wanita dan masaalah-masaalah perhubungan / Raja Nor Dina Mohar - Raja Nor Dina, Mohar (1976)
The main reason in carrying out this research is to test the hypothesis that relational problem is a factor that is found more among delinquent girls than delinquent boys. The paper focuses on three specific predictions relating female delinquency to relational problems and that delinquent girls would be most likely to: 1. Come from broken homes; 2. Come from families with many family tensions; and 3. Be rated low in personal appearance and in grooming skills. By relational problem, it means any problem which would hinder a girl in her ability to establish and maintain satisfying relation ship. A broken home for example, would hinder a girl in relational satisfaction in a variety of ways. In the first place, she would be cut off from one vital parental relationship. Further ore, whichever parent was missing, the girl would not have in her mother a modal who was able to establish and maintain a happy and stable marital relationship. Finally, except for hones broken by death, broken home are before the break more filled with tensions than are unbroken home. A family in which tensions are high not only has unsatisfactory present relationship but also cannot help the children develop the relational skills necessary to forming other satisfying relationships.